2021
DOI: 10.1002/aisy.202100081
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Hydrogels with Improved Actuation Function by Interconnected Microchannels

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/aisy.202100081.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…For all agarose hydrogels, regardless of the presence of microchannels, the compressive strength and modulus decreased with increasing pH, while failure strain increased. This behavior is consistent with a previous study, [ 36 ] in which higher porosity was observed for hydrogels in basic solutions, leading to less resistance to compression. Hydrogels containing cavitated microchannels displayed slightly reduced maximum compressive strength, compressive modulus, and failure strain compared to hydrogels without cavitated microchannels (Figure 5A; Table S3, Supporting Information).…”
Section: Resultssupporting
confidence: 93%
“…For all agarose hydrogels, regardless of the presence of microchannels, the compressive strength and modulus decreased with increasing pH, while failure strain increased. This behavior is consistent with a previous study, [ 36 ] in which higher porosity was observed for hydrogels in basic solutions, leading to less resistance to compression. Hydrogels containing cavitated microchannels displayed slightly reduced maximum compressive strength, compressive modulus, and failure strain compared to hydrogels without cavitated microchannels (Figure 5A; Table S3, Supporting Information).…”
Section: Resultssupporting
confidence: 93%
“…[18,19] The deswelling results in a volume change that can be used for actuation. However, due to slow response rates (e.g., 12% deswelling within 10 min [20] ), limiting work output and cycle rate, the properties of bulk PNIPAM hydrogels are not meeting the high requirements needed for soft actuators. In addition to the poroelastic limit, for PNIPAM these limitations are related to the formation of a dense "skin layer" [21] during the deswelling process, which greatly reduces the water diffusion out of the hydrogel, requiring weeks to reach equilibrium deswelling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the actuation effect, including actuation dynamics as well as stroke forces, can be improved by introducing pores into the material. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Whereas in previous studies template-assisted methods have proven highly suitable for introducing pores into hydrogels, they lack local microstructural control, while being excellent for structuring macroscopic samples with an interconnected structure. [10] For generating highly efficient pNIPAM-based microactuators, a precisely defined design is required and thus methods are needed that allow for their highly precise 3D structuring at the micrometer scale.The technology of additive nano-and micromanufacturing opens doors to novel and remarkable microengineering possibilities and even enables printing of simple 3D volumetric structures at small scales. [12] Direct laser writing (DLW) involving two-photon polymerization of photoresists is one of the additive manufacturing techniques that can be used to fabricate intricate and miniaturized 3D structures, as they are required for the fabrication of microactuators.…”
mentioning
confidence: 99%
See 1 more Smart Citation